CEO Behavior and Firm Performance - Bandiera, O; Hansen, S; Prat, A; Sadun, R (2018)
We develop a new method to measure CEO behavior in large samples via a survey that collects high-frequency, high-dimensional diary data and a machine learning algorithm that estimates behavioral types. Applying this method to 1,114 CEOs in six countries reveals two types: “leaders” who do multi-function, high-level meetings, and “managers” who do individual meetings with core functions. Firms that hire leaders perform better, and it takes three years for a new CEO to make a di↵erence. Structural estimates indicate that productivity di↵erentials are due to mismatches rather than leaders being better for all firms.